Microstructure and wear of FeCrC, SiC and B4C coated AISI 430 stainless steel - Gur, Ali Kaya; Yildiz, Tulay; Kati, Nida; Kaya, Sinan (Carl Hanser Verlag, 2019)
The Taguchi procedure is an important method for obtaining high quality without increasing the cost in the optimization of the process parameters. In the Taguchi procedure, the orthogonal planes of the maximum effects of the controllable process parameters and the minimum effects of the uncontrollable process parameters were used. In this study, B4C, SIC, and FeCrC powders were alloyed on the surface of an AISI 430 ferritic stainless steel by plasma transfer arc (PTA) welding. The abrasive wear of the various specimens was measured by the mass loss at a load between 10 and 16 N using SiC abrasive paper with a 60 and 240 mesh and over distances between 20 and 30 meters. The effects of the parameters with respect to the lowest wear behavior as an important criterion were optimized by the lowest-the best control characteristic of the Taguchi method. The results were analyzed by graphical methods.
Keywords: Wear; microstructure; stainless steel; carbide coating